Spam filtering implementation using open source software / Ahmad Bakhtiar Ibrahim - Ibrahim, Ahmad Bakhtiar (Faculty of Information Technology and Quantitative Sciences, 2006)
Spam is a serious problem that has been increasing plaguing users of the Internet. Programs known as spam filters are employ to assist the user in deciding if an email is worth reading or not. This paper is focuses on build the mail server with spam filter and analysis the effectiveness of rule based (Heuristic) and Bayesian filtering method that use in SpamAssassin. The mail server consolidates software which is available in public domain as a powerful and low cost solution for seeking option in fighting spam. The rule based method using set of rules to define the incoming email as spam or not and Bayesian method using probability of incoming mail to define that the mail is belong to either spam or legitimate mail category after its require a training period for SpamAssassin. The combination of both methods show that SpamAssassin is a better spam checking.